JEJAK KEBUDAYAAN PERSIA DI KAWASAN TINGGALAN SEJARAH SAMUDRA PASAI - Taqiyuddin Muhammad (Sharia and Law Faculty, 2017)
This review article traces the history of Persian civilization and culture in the archipelago with researching the various inscriptions are found in a variety of headstones and other historical evidence contained in the living history of Samudera Pasai.